The Pathogenicity of Pseudomonas syringae MB03 against Caenorhabditis elegans and the Transcriptional Response of Nematicidal Genes upon Different Nutritional Conditions - Ali, Muhammad; Sun, Yu; Xie, Li; Yu, Huafu; Bashir, Anum; Li, Lin (Frontiers in Microbiology, 2016)
Different species of the Pseudomonas genus have been reported for their pathogenic potential against animal cells. However, the pathogenicity of Pseudomonas syringae against Caenorhabditis elegans has never been reported. In this study, the interaction of P. syringae MB03 with C. elegans was studied. Different bioassays such as killing assay, lawn leaving assay, food preference assay, L4 growth assay and newly developed “secretion assay” were performed to evaluate the pathogenic potential of P. syringae on different growth media. The results of the killing assay showed that P. syringae MB03 was able to kill C. elegans under specific conditions, as the interaction between the host and the pathogen varied from non-pathogenic (assay on NGM medium) to pathogenic (assay on PG medium). The lawn leaving assay and the food preference assay illustrated that C. elegans identified P. syringae MB03 as a pathogen when assays were performed on PG medium. Green fluorescent protein was used as the reporter protein to study gut colonization by P. syringae MB03. Our results suggested that MB03 has the ability to colonize the gut of C. elegans. Furthermore, to probe the role of selected virulence determinants, qRT-PCR was used. The genes for pyoverdine, phoQ/phoP, phoR/phoB and flagella were up regulated during the interaction of P. syringae MB03 and C. elegans on PG medium. Other than these, the genes for some proteases, such as pepP, clpA and clpS, were also up regulated. On the other hand, kdpD and kdpB were down regulated more than 3-fold in the NGM - C. elegans interaction model. The deletion of the kdpD and kdpE genes altered the pathogenicity of the bacterial strain against C. elegans. Overall, our results suggested that the killing of C. elegans by P. syringae requires a prolonged interaction between the host and pathogen in an agar-based assay. Moreover, it seemed that some toxic metabolites were secreted by the bacterial strain that were sensed by C. elegans. Previously, it was believed that P. syringae could not damage animal cells. However, this study provides evidence of the pathogenic behavior of P. syringae against C. elegans.